Market of grains in Ukraine: analysis of the modern state - Vashenko, I. (Land Management, Cadastre and Land Monitoring, 2018)
Abstract. In a market economy, there is a need for Ukraine's integration into the world economic space, the search for stable niches in the sale of manufactured products. Taking into account the fact that one of the leading branches of international specialization of the country is agricultural production, strengthening of the positions on the world market of agricultural products is one of the state's top priorities.Today in the world there are three main resources that determine the prospects for the development of countries for the future: drinking water, grain and oil. The cereal sector has a significant impact on the welfare of the rural population and the development of rural areas and is the basis for most sectors of the agro-industrial complex of Ukraine.In the agrarian market, grain crops retain leading positions in exports, processing and domestic consumption, proving their strategic importance in ensuring food and economic security of the country.The strategic nature and scale of the development of the domestic grain industry are complemented by its significant inter-sectoral links with other sectors of the national economy, which has a significant impact on the overall state of the entire economy of the country.Keywords. Cereals, market, agriculture, yield, gross tax.